Endophytic fungi improve management of the burrowing nematode in banana (Musa spp.) through enhanced expression of defence-related genes - Kisaakye, J.; Fourie, H.; Coyne, D.; Cortada, L.; Khamis, F.M.; Subramanian, S.; Masinde, S.; Haukeland, Solveig (Brill, 2023)
The root-burrowing nematode, Radopholus similis, is reputedly the most damaging nematode pest of banana and responsible for major production losses. In this study, the endophytic potential of 13 fungal isolates was assessed for the management of R. similis in East African Highland bananas (‘Ng’ombe’). All isolates successfully colonised tissue-cultured banana roots, with isolates from Trichoderma, Fusarium and Hypocrea producing the highest (⩾49.1%) and Beauveria isolates the lowest (⩽14.4%) colonisation. The fungal endophytes T. asperellum (ICIPE 700) and H. lixii (ICIPE 697) were the most effective in reducing R. similis densities (>81%) relative to the non-inoculated control. However, the combined inoculation of ICIPE 700 and ICIPE 697 led to greater suppression of R. similis (>21%) relative to individual inoculation. Suppression of R. similis following inoculation of banana roots with ICIPE 700 and/or ICIPE 697 was associated with the significant upregulation of the defence-related gene PR-1, the cell signalling gene calmodulin Ca2+ and the cell-wall-strengthening gene β-1,3-glucan synthase. This study demonstrates the potential for nematode management in bananas with fungal endophytes, especially using the isolates ICIPE 700 and ICIPE 697 when combined.